Development of an open source tool for learning Linux - Babaghayou, Abdelkader; Belabbaci, Amel, Directeur de thèse (Laghouat : Université Amar Telidji - Département d'informatique, 2024)
Learning Linux can be challenging for new users due to its complexity.This thesis propose an open source tool that comes as a web application designed to make learning Linux easier and more engaging especially for beginners.The application features a visual interface that helps users practice key Linux concepts and commands through an interactive terminal emulator . this tool aims to simplify the learning process and improve how beginners grasp essential Linux skills and test various commands without harming their own system . Testing showed that users found emulators to be a valuable resource, making it easier to practice and use Linux.